Hypertension Nursing Care for The Elderly: A Case Report - Ridwan, Ali; Sari, Yeni Kartika; Romadhon, Wimar Anugerah (Health Gate, 2025)
Hypertension in the elderly is a condition marked by increased blood pressure due to age-related physiological changes. Common symptoms include headaches, dizziness, blurred vision, fatigue, and chest pain, which serve as subjective data for formulating nursing diagnoses. The aims of this case study is to analyze nursing care for elderly patients with hypertension at the independent nursing practice in Karang Bendo Village, Ponggok District.. The method used is a case study involving four elderly respondents who received comprehensive nursing care, covering assessment, diagnosis, intervention planning, implementation, and evaluation. The respondents had a 4–7-year history of hypertension, with complaints such as dizziness, fatigue, headaches, tingling, and sleep disturbances. Blood pressure readings ranged from 140/85 to 160/95 mmHg. Identified nursing diagnoses included acute pain, risk of falls, fatigue, and disturbed sleep patterns. Nursing interventions were evaluated after each session, showing improved patient conditions and positive outcomes. This case study contributes to the development of geriatric nursing theory, particularly in managing hypertension in older adults, and provides additional evidence of the effectiveness of nursing interventions in controlling blood pressure in the elderly.